Religiosity and depression in the United States older adult population : an analysis of the influence of type of religiosity, race, and gender - McKee, Adam (My University, 2012)
The purpose of this study was to analyze the relationship between the two types of religiosity (organizational and nonorganizational) and depression in the United States older adult population. This study is rooted in psychological, sociological, and gerontological research dating back to the early 1950s with the pioneering work of Moberg (1953a). The study used information obtained from the Religion, Aging, and Health Survey (Krause, 2001); the final sample size consisted of 1,370 participants. Results show limited but significant efficacy of both organizational and nonorganizational religiosity, gender and race against depression. This project supports the already abundant literature showing that women have higher levels of depression than men, and African Americans report more depression than Caucasians, but this racial difference may be mitigated by attending religious services.--Abstract."
Keywords: Depression in old age; Depression in women; Depression, Mental; Depression, Mental